Sustainable system design of electric powertrains—comparison of optimization methods. Issue 9 (2nd September 2022) - Leise, Philipp; Eßer, Arved; Eichenlaub, Tobias; Schleiffer, Jean-Eric; Altherr, Lena C.; Rinderknecht, Stephan; Pelz, Peter F.
Abstract : The transition within transportation towards battery electric vehicles can lead to a more sustainable future. To account for the development goal 'climate action' stated by the United Nations, it is mandatory, within the conceptual design phase, to derive energy-efficient system designs. One barrier is the uncertainty of the driving behaviour within the usage phase. This uncertainty is often addressed by using a stochastic synthesis process to derive representative driving cycles and by using cycle-based optimization. To deal with this uncertainty, a new approach based on a stochastic optimization program is presented. This leads to an optimization model that is solved with an exact solver. It is compared to a system design approach based on driving cycles and a genetic algorithm solver. Both approaches are applied to find efficient electric powertrains with fixed-speed and multi-speed transmissions. Hence, the similarities, differences and respective advantages of each optimization procedure are discussed.